The rise of the state : profitable investing and geopolitics in the 21st century - Mostrous, Yiannis G. (FT Press, 2011)
If you want to make money in the coming decade, you need to understand the two most powerful trends that are reshaping global markets right now: the growth of emerging economies, and the accelerating influence of sovereign wealth funds. Both trends share one crucial characteristic: they reflect the rising role of government actors, and make it more important for investors to understand geopolitics than ever before. These trends emerged well before the global financial and economic crisis, and that crisis has only strengthened them. In The Rise of the State , three leading investment advisors tell the hidden story of state investment power, and offer more than 70 specific investment recommendations you can start profiting from right now. The authors illuminate trends ranging from the new rise of Asia to the massive migration of individuals to cities worldwide - identifying implications and opportunities in areas ranging from energy to water, healthcare to education. You'll find powerful new insights into the surprising - and mostly positive - impact of sovereign wealth funds both within and outside the U.S. You'll also learn how to ride alongside these funds, understand their goals and strategies, and invest in the companies and industries they've identified as offering the greatest potential.